Clinical symptoms, diagnosis and application of stenting and coronary angiography practices of coronary heart diseases - Umarkulov Mukhtarali; Burkhonova Orzukhan (Zien Journals, 2023)
This article discusses heart disease mainly coronary heart disease. The author gives some information about the causes, clinical forms, diagnosis and treatment of coronary heart diseases
Keywords: stenting; symptoms of heart disease; excess weight